If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 11 = x + 1 Reorder the terms: 11 + 4x = x + 1 Reorder the terms: 11 + 4x = 1 + x Solving 11 + 4x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 11 + 4x + -1x = 1 + x + -1x Combine like terms: 4x + -1x = 3x 11 + 3x = 1 + x + -1x Combine like terms: x + -1x = 0 11 + 3x = 1 + 0 11 + 3x = 1 Add '-11' to each side of the equation. 11 + -11 + 3x = 1 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 1 + -11 3x = 1 + -11 Combine like terms: 1 + -11 = -10 3x = -10 Divide each side by '3'. x = -3.333333333 Simplifying x = -3.333333333
| 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 | | 3x-5x-120=0 | | -6n+3=-9 | | 2x-44=4x-88 | | 4n+10=2n-5 | | N-6=21-8n | | 9x+10y=500 | | (n-6)+6=12 | | (m-1)x^2-(m-1)x+m+5=0 | | 3(f+1)=6 | | X^3=2x-38 | | 3(b+1)+3=18 | | 6=3n(n-5) | | g-8/-2=-3 | | 3(w+5)-6=15 | | 2(z+2)=20 | | X^3-2x+38=0 |